PENDAMPINGAN PENELITIAN TINDAKAN KELAS BAGI MAHASISWA MADRASAH DINIYAH - Aisida, Sufinatin; Adibah, Adibah (ABDINA: Jurnal Sosial dan Pengabdian kepada Masyarakat, 2025)
Human resources who are superior and ready to compete in the changing times of the 21st century are the key to quality education. This can happen if the quality of educators is able to conduct research well, the smallest thing is to understand how learning in their class reflects and finds solutions to these problems. One of them is with class action research. The purpose of this mentoring activity is to provide PTK assistance to overcome the difficulties experienced by Madin students. This service activity uses the partisipatori method which consists of three stages, namely planning, implementation, and evaluation. Based on the results of this mentoring activity, it shows that the madin students are very enthusiastic about the PTK assistance that has been provided by the Service team so that this activity can run well and produce real work in carrying out PTK. The results of the evaluation of the PTK presentation and report were in accordance with the theory and principles of PTK by 84.62%, while 15.38% were due to other factors. This shows that there is an increase in knowledge and understanding of PTK, the ability to identify problems and critically find solutions and actions to their class problems, the big impact is to increase the professionalism of Madin students who are also Madin teachers. This assistance is expected to make the learning process in the classroom more innovative, fun and meaningful.